Direct comparison of a radioiodinated intact chimeric anti-CEA MAb with its F(ab')2 fragment in nude mice bearing different human colon cancer xenografts. - Vogel, C. A. (Nature Publishing Group, 1993)
Tumour localisation and tumour to normal tissue ratios of a chimeric anti-carcinoembryonic antigen (CEA) monoclonal antibody (MAb), in intact form and as an F(ab')2 fragment labelled with 125I and 131I, were compared in groups of nude mice bearing four different colon cancer xenografts, T380, Co112 or LoVo, of human origin, or a rat colon cancer transfected with human CEA cDNA, called '3G7'. For each tumour, three to four mice per time point were analysed 6, 12, 24, 48 and 96 h after MAb injection. In the different tumours, maximal localisation of intact MAb was obtained at 24 to 48 h, and of F(ab')2 fragment 12 to 24 h after injection. Among the different tumours, localisation was highest with colon cancer T380, with 64% of the injected dose per gram (% ID/g) for the intact MAb and 57% for its F(ab')2 fragment, while in the three other tumours, maximal localisation ranged from 14 to 22% ID g-1 for the intact MAb and was about 11% for the F(ab')2. Tumour to normal tissue ratios of intact MAb increased rapidly until 24 h after injection and remained stable or showed only a minor increase thereafter. In contrast, for the F(ab')2 fragment, the tumour to normal tissue ratios increased steadily up to 4 days after injection reaching markedly higher values than those obtained with intact MAb. For the four different xenografts, tumour to blood ratios of F(ab')2 were about 2, 3 and 5 to 16 times higher than those of intact antibodies at 12, 24 and 96 h after injection, respectively.